Effect of Banana Homogenate on Shoot Regeneration of Ciplukan (Physalis angulata L.) - Varni Apensa; Retno Mastuti (Journal of Experimental Life Science)
In vitro culture techniques can be used as an alternative problem solving in an effort to provide Ciplukan plant as a raw material of herbal medicine in a sustainable manner. The purpose of this study was to observe the effect of banana homogenate (BH) added into culture medium on shoot regeneration of Ciplukan (Physalis angulata L.) and plantlet development until acclimatization stage. The experimental design used was a randomized factorial group. The first factor was the two varieties of banana fruit namely, Ambon and Raja. The second factor was concentration of BH with four levels, 0 (control), 2.5%, 5% and 7.5 % and each treatment combination was repeated five times. Explant used in this research was the third node of 2 weeks old in vitro shoot after subculture to MS0 medium. Data analysis used ANOVA test. Eight week after culture (WAC) medium containing BH induced higher number of shoot compare to medium without BH. The addition of 5% BH var. Ambon had significant effect on increasing shoot number. Well rooted plantlets produced in MS0 rooting medium also showed high survival rate (66.7%< - 100%) two weeks after transferred to greenhouse. Therefore, the addition of BH into in vitro medium can be an alternative method for micropropagation of Ciplukan.